Fabrication of Carbon Nanotube/TiO2 Composite Photocatalysts and Their Electro-photolysis for Organic Dye - ZHANG, F.J.; CHEN, M.L.; OH, W.C. (Asian Journal of Chemistry, 2010)
In present work, the improved performance of carbon nanotube/ TiO2 structure electrode for organic dye has been studied. The composite electrodes consisting of carbon nanotubes (CNTs) and a titanium oxide matrix with phenol resin binder was fabricated by means of mixture method. The chemical and morphological structure of CNT/TiO2 composites were characterized by means of BET surface area, X-ray diffraction (XRD), scanning electron microscope (SEM), Raman spectroscopy and energy dispersive X-ray (EDX). The electrode showed a remarkably enhanced performance for methylene blue oxidation under UV illumination with or without electro-chemical reaction. Such a remarkably improved performance of the CNT/TiO2 structure electrode might be due to the enhanced methylene blue oxidation by electro- and photogenerated electrons and holes in the CNT and TiO2 under UV illumination with or without electro-chemical reaction.